2020
DOI: 10.23876/j.krcp.19.035
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens of peritoneal dialysis peritonitis: Trends from a single-center experience over 15 years

Abstract: Peritoneal dialysis (PD) is one of the options for renal replacement therapy in end-stage renal disease patients. While it has many advantages over hemodialysis (HD), there are several limitations. Infectious complications such as peritonitis are still major causes of PD technical failure [1-5] which reduces patient quality of life [2-4,6]. It is important to explore recent trends in microbiology to select the appropriate empirical treatment for PD peritonitis. Historically, Staphylococcus epidermidis and Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…This is basically consistent with the results of Hwang et al. [ 8 ]. The number of gram-negative bacterial peritonitis episodes in the 2014–2018 group was significantly higher than that in the 2009–2013 group, which is consistent with the conclusion that gram-negative bacterial peritonitis has demonstrated an increasing trend, which has been reported by several countries and regions [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is basically consistent with the results of Hwang et al. [ 8 ]. The number of gram-negative bacterial peritonitis episodes in the 2014–2018 group was significantly higher than that in the 2009–2013 group, which is consistent with the conclusion that gram-negative bacterial peritonitis has demonstrated an increasing trend, which has been reported by several countries and regions [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…This rate was reported as 59.2% by Ponce et al In addition, the detection rate of gram‐positive and gram‐negative organisms was found similar to that study [15]. Although there is a study showing that the culture negativity rate has improved significantly in recent years [22], although our study covers the years between 2015 and 2020, the rate of culture negativity is still very high. Although Dotis et al found the rate of gram positivity as 65.2% in pediatric patients who underwent APD, the number of patients included in the study and the number of peritonitis episode were very low [13].…”
Section: Discussionsupporting
confidence: 86%
“…The sources of these variations may be center-related factors, such as center size, topical antibiotic prophylaxis, and PD training [2]. To date, few articles describe the chronological changes in peritonitis rates, and most reports are from a single center [12,[14][15][16][17]. In our multicenter study, we demonstrated a significant decrease in the peritonitis rate during the study period, especially over the last 3 years, which could be attributable to the significant decrease in G+ PDAP, G-PDAP, and culture-negative PDAP rates.…”
Section: Discussionmentioning
confidence: 99%